Family Coaching in Stunting Prevention Efforts in Central Kalimantan - Ummi Umairoh; Putri Nur Anggraini; Hendy Pratama Putra; Muhammad Zahid Al-anshory; Kamal Iktibar Ramadhan; Anas Maulana (Mir'ah: Family Law and Legal Culture, 2024)
This research aims to analyze the role of family development in efforts to reduce stunting rates in Central Kalimantan, where obstacles exist in family development faced with various unique challenges, such as high divorce rates, problems of child malnutrition (stunting), underage marriage, poverty, domestic violence, child legal cases, and drug abuse. The research method uses empirical methods, namely field data collection with a research approach using a sociolegal approach in offering an understanding of the social dynamics of family coaching by the National Population and Family Planning Agency (BKKBN) in preventing stunting. The results show that family development has a very crucial role in preventing stunting. Programs such as BKB, BKR, and BKL have provided parents with knowledge and skills in parenting. However, there are still several factors that influence fluctuations in stunting rates, such as socioeconomic conditions and the pandemic. Therefore, more comprehensive and sustainable efforts are needed to reduce stunting rates in Central Kalimantan.